AML in the Molecular Age: From Biology to Clinical Management - Celalettin Ustun (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
We appreciate your willingness to contribute an article to the upcoming Special Issue of the Journal of Clinical Medicine, which will focus on "AML in the Molecular Age: From Biology to Clinical Management". In this Special Issue, we aim to discuss important scientific and clinical ongoing activities in AML. Scientific subjects will include articles concerning the molecular abnormalities, epigenetic mechanisms of disease/therapy as well as the role of the immune system in AML. Very interesting and uncommon subjects will include discussions of extramedullary disease and evaluations of the central nervous system by various imaging techniques. Experts will describe the role of hypomethylating agents in the management of AML and currently emerging and promising investigational therapies. Specifics of treament of pediatric and younger patients with AML. Clinical success relies greatly on supportive therapy, and we will discuss supportive therapy, including infection prophylaxis. Allogeneic hematopoietic stem cell transplantation remains the most effective measure for curing aggressive AML, and a variety of topics will be considered: donor selection, age of recipient, which has been increasing seemingly without limit; therefore, recipient/donor assessments are more important than ever in the aging population. Alternative donor use (e.g., cord blood and haploidentical individuals) has been increasing dramatically; when and who should be considered, what is being investigated? With signiﬁcant changes occurring with respect to both donors and recipients, the pros and cons of using of anti-thymocyte globulin use in conditioning regimens will be also described.